Educational mobility and telomere length in middle-aged and older adults: testing three alternative hypotheses. (1st October 2020) - Cuevas, Adolfo G.; Greatorex-Voith, Siobhan; Abuelezam, Nadia; Eckert, Natalie; Assari, Shervin
ABSTRACT: Critical period, social mobility, and social accumulation are three hypotheses that may explain how educational mobility impacts health. Thus far, there is little evidence on how these processes are associated with biological aging as measured by telomere length. Using cross-sectional data from the 2008 Health and Retirement Study, we examined the association between educational mobility (parental education and contemporaneous education) and telomere length. The final model is adjusted for sociodemographic factors and socioeconomic status, childhood adversity, and health behaviors/risk factors, as well as depressive symptoms. A total of 1, 894 participants were included in the main analyses. High parental education was associated with longer telomere length in a fully adjusted model (B = 0.03, CI [0.002, 0.07]). Downwardly mobile individuals (high parental education and low contemporaneous education) had longer telomere length compared to stably low individuals in a fully adjusted model (B = 0.05, CI [0.004, 0.09]). There was support for the critical period hypothesis and partial support for the change hypothesis. There was no evidence to support the social accumulation hypothesis. Prospective studies are needed to understand the mechanism that can help further explain the association between educational mobility and telomere length.